Efektivitas Penerapan Program Pembiasaan Diri Berbasis Nilai-Nilai Agama Untuk Meningkatkan Kedisiplinan Siswa Kelas (X) MA Al-Ahliyah (Studi Kasus: Keterlambatan Sholat Berjamaah) - Dewi, Ratna; Bagus, Solihah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to determine the effectiveness of a self-habituation program based on religious values in improving student discipline, particularly regarding delays in performing congregational prayers among Grade X students at MA Al-Ahliyah. The research employs a qualitative approach with a case study design. Data collection techniques include observation, in-depth interviews, and documentation. The results indicate that the self-habituation program, implemented through regular religious activities such as congregational prayers, Qur'an recitation, and spiritual guidance, positively impacts students' discipline. Although some challenges remain, such as lack of personal awareness and suboptimal supervision, the program is generally effective in shaping students' disciplined character. It is recommended that the school maintain consistent implementation and conduct regular evaluations of the program.